Business Impact Analyst (BIA) session runner - Yee Chee, Kang (2013)
BUSINESS IMPACT ANLYST (BIA) is a system that been essential in being a part of business continuity. As business continuity is management that have been take over the company when emergency situation like fire, flood and other incident take place. This process which called as business continuity plan haven taken to recover the company normal flow to avoid massive loss in the incident. BIA is a part of the business continuity plan which to indicate the critical level of the department in the company so that Business Continuity Management (BCM) know how to plan for the recover in the limited time. In reality, the BIA process is start when BCM coordinator have set the survey question and assign one staff of every different department in the company. The staff have being assigned is called Business Continuity Plan (BCP) coordinator unit. BCP coordinator unit will insert the required data into survey from.BCM coordinator will later analyst and know which the critical level department is. The system in this project will help BCM coordinator to be setting the template and question in the form for gaining the required data and also help BCP coordinator unit more easily to insert the data.